Next generation sequencing: an application in forensic sciences?. (3rd October 2017) - Alvarez-Cubero, Maria Jesus; Saiz, Maria; Martínez-García, Belén; Sayalero, Sara M.; Entrala, Carmen; Lorente, Jose Antonio; Martinez-Gonzalez, Luis Javier
Abstract: Context: Over the last few decades, advances in sequencing have improved greatly. One of the most important achievements of Next Generation Sequencing (NGS) is to produce millions of sequence reads in a short period of time, and to produce large sequences of DNA in fragments of any size. Libraries can be generated from whole genomes or any DNA or RNA region of interest without the need to know its sequence beforehand. This allows for looking for variations and facilitating genetic identification. Objectives: A deep analysis of current NGS technologies and their application, especially in forensics, including a discussion about the pros and cons of these technologies in genetic identification. Methods: A systematic literature search in PubMed, Science Direct and Scopus electronic databases was performed for the period of December 2012 to June 2015. Results: In the forensic field, one of the main problems is the limited amount of sample available, as well as its degraded state. If the amount of DNA input required for preparing NGS libraries continues to decrease, nearly any sample could be sequenced; therefore, the maximum information from any biological remains could be obtained. Additionally, microbiome typification could be an interesting application to study for crime scene characterisation. Conclusions: NGS technologies are going to be crucial for DNA human typing in cases like mass disasters or other events where forensic specimens and samples are compromised and degraded. With the use of NGS it will be possible to achieve the simultaneous analysis of the standard autosomal DNA (STRs and SNPs), mitochondrial DNA, and X and Y chromosomal markers.